Debt overhang and deleveraging in the US household sector: gauging the impact on consumption - Bruno Albuquerque; Georgi Krustev (European Central Bank (ECB), 2015)
Using a novel dataset for the US states, this paper examines whether household debt and the protracted debt deleveraging help explain the dismal performance of US consumption since 2007 in the aftermath of the housing bubble. By separating the concepts of deleveraging and debt overhang - a flow and a stock effect - we find that excessive indebtedness exerted a meaningful drag on consumption over and beyond income and wealth effects. The overall impact, however, is modest - around one-sixth of the slowdown in consumption between 2000-06 and 2007-12 - and mostly driven by states with particularly large imbalances in their household sector. This might be indicative of non-linearities, whereby indebtedness begins to bite only when misalignments from sustainable debt dynamics become excessive.
Keywords: C13; C23; C52; D12; H31; 330; Consumption function; Debt overhang; Household deleveraging; Housing wealth